Development and mechanical characterization of eggshell bio-filler reinforced bamboo fiber composites - Afroz Khan; B. K. Naveen Kumar; K. J. Anand; E. Ashoka; G. Hareesha (Fracture and Structural Integrity)
Hybridization of natural fiber composite by incorporating waste- derived fillers has been identified as a promising sustainable technique to develop environmentally friendly and economical composites with enhanced mechanical properties. This study explores the mechanical performance of hybrid bamboo-epoxy composites incorporated with bio filler derived from waste chicken eggshells. Compression molding was employed to develop unfilled and eggshell powder filled bamboo composites by varying eggshell content (2, 4, and 6 wt%) while maintaining constant bamboo fiber wt%. Composites were tested for mechanical properties by performing tensile test, flexural test, and impact test per ASTM standards. Results indicated that eggshell filler inclusion significantly modifies the tensile, flexural, and impact strength properties of base bamboo composite. Adding eggshell filler enhanced tensile and flexural properties which was attributed to improved interfacial bonding and efficient stress transfer. Optimal filler was achieved for composites with 4 wt % eggshell exhibiting 13.5% improvement in tensile strength and 16.4% improvement in flexural strength. While reduction in impact strength observed was attributed to incorporation of inorganic eggshell filler which mainly consists of CaCo3 content. The fractography studies revealed the improved fiber-matrix interaction with the inclusion of filler, reduced fiber pullouts, and failure by fiber breakage supporting the observed experimental results